A Hierarchical Copper Oxide–Germanium Hybrid Film for High Areal Capacity Lithium Ion Batteries - Deng, Liying; Li, Wangyang; Li, Hongnan; Cai, Weifan; Wang, Jingyuan; Zhang, Hong; Jia, Hongjie; Wang, Xinghui; Cheng, Shuying (Frontiers in Chemistry, 2020)
Self-supported electrodes represent a novel architecture for better performing lithium ion batteries (LIBs). However, lower areal capacity restricts their commercial application. Here, we explore a facial strategy to increase the areal capacity without sacrificing the lithium storage performance. A hierarchical CuO-Ge hybrid film electrode will not only provide high areal capacity but also outstanding lithium storage performance for LIB anode. Benefiting from the favorable structural advance as well as the synergic effect of the Ge film and CuO NWs array, the hybrid electrode exhibits a high areal capacity up to 3.81 mA h cm-2, good cycling stability (a capacity retention of 90.5% after 150 cycles) and superior rate performance (77.4% capacity remains even when the current density increased to 10 times higher)